2011
DOI: 10.3389/fnagi.2011.00007
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation at CA3–CA1 Hippocampal Synapses with Special Emphasis on Aging, Disease, and Stress

Abstract: Synaptic plasticity in the mammalian central nervous system has been the subject of intense investigation for the past four decades. Long-term potentiation (LTP), a major reflection of synaptic plasticity, is an activity-driven long-lasting increase in the efficacy of excitatory synaptic transmission following the delivery of a brief, high-frequency train of electrical stimulation. LTP is regarded as a principal candidate for the cellular mechanisms involved in learning and offers an attractive hypothesis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 523 publications
(671 reference statements)
5
94
0
3
Order By: Relevance
“…Interestingly, this effect was seen for both up-and downregulated genes ( Figure 1I). Functional enrichment analysis showed that age-associated increases in gene expression were linked to inflammatory processes, while decreases represented pathways linked to metabolism and transcriptional response ( Figure 1J Interestingly, we did not find any pathways linked to synaptic plasticity, which is known to decrease in the aging brain (23). These data suggest that the impact of aging on gene expression and the effect of SAHA are likely to be complex.…”
Section: Introductionmentioning
confidence: 52%
“…Interestingly, this effect was seen for both up-and downregulated genes ( Figure 1I). Functional enrichment analysis showed that age-associated increases in gene expression were linked to inflammatory processes, while decreases represented pathways linked to metabolism and transcriptional response ( Figure 1J Interestingly, we did not find any pathways linked to synaptic plasticity, which is known to decrease in the aging brain (23). These data suggest that the impact of aging on gene expression and the effect of SAHA are likely to be complex.…”
Section: Introductionmentioning
confidence: 52%
“…It has been reported that long-term potentiation (LTP), a form of synaptic plasticity characterized by a persistent increase in excitatory synaptic strength and regarded as a potential cellular model of learning (Kumar, 2011), is enhanced in the Schaffer collateral-CA1 synapses of the mSOD1 mouse hippocampus (Spalloni et al, 2006). From these data it was inferred that presymptomatic mSOD1 mice have an enhancement of hippocampal functionality that provides favorable conditions for spatial information processing.…”
Section: Discussionmentioning
confidence: 74%
“…There is voluminous evidence that deficient NMDAR‐dependent LTP results in learning and memory impairments (David Sweatt, 2009) and that hippocampal LTP declines with age (Lynch, 2010; Kumar, 2011). Moreover, the rapid recruitment of NMDA receptor subunits can reduce the threshold for LTP, a process that appears to be dependent on dendritic mRNA translation (Swanger et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%